2010
DOI: 10.5746/leia/10/v1/a06/nguyen_franken
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Language Input in Second Language Acquisition: A Case of Vietnamese EFL Teachers

Abstract: The importance of incorporating second language acquisition (SLA) research into second language teacher education and classroom practice has been recognised (Ellis, 2005;Tarone & Allwright, 2005). However, this is a challenge as exemplified in task-based language teaching (TBLT), which closely draws on SLA research. The present study focuses specifically on one area of SLA, language input. By using a multimethod case study approach, it documents six Vietnamese EFL teachers' conceptions of input. The study gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Even with this freedom and the adoption of more communicative textbooks, traditional form-focused instruction is common. For example, Le and Barnard (2009) and Nguyen and Franken (2010) found that most of their teacher participants spent a large portion of their lessons explicitly teaching vocabulary and grammar, and frequently delayed communicative activities until their students were familiar with the language content of the lesson. Similarly, found that the three university EFL teachers that the study focused on consistently followed the PPP approach and taught grammar structures.…”
Section: Research On the Implementation Of Task-based Teaching In Vietnammentioning
confidence: 99%
“…Even with this freedom and the adoption of more communicative textbooks, traditional form-focused instruction is common. For example, Le and Barnard (2009) and Nguyen and Franken (2010) found that most of their teacher participants spent a large portion of their lessons explicitly teaching vocabulary and grammar, and frequently delayed communicative activities until their students were familiar with the language content of the lesson. Similarly, found that the three university EFL teachers that the study focused on consistently followed the PPP approach and taught grammar structures.…”
Section: Research On the Implementation Of Task-based Teaching In Vietnammentioning
confidence: 99%
“…At university level, Nguyen and Franken (2010), explored six teachers' understandings of the roles of input, output, and interaction in TBLT through interviews and classroom observation.…”
Section: The Implementation Of Tblt By Vietnamese Teachersmentioning
confidence: 99%